Surgeon doctors performance appraisal system: A case study of Z Hospital in Guangzhou - Zijie, Mai (2014)
By using management, finance, statistics, operations research methods,hospital performance appraisal is a comprehensive comparison analysis to customer service, service quality of hospital, operational efficiency, scientific research and the connotation construction and other various aspects, aimed tomake an objective and fair evaluation of the department and individual. Performance management is one of the important functionsof modern hospital management, and is also an important means to reflect the status of hospital performance management, it has a positive guiding role to promote the development of the hospital. Buildup performance appraisal system, through an objective and fair performance evaluation, helps to guide the hospital introducing competition mechanism, strengthen management consciousness, strengthen the connotation construction, implementthescientific management, promote the continuous improvement of social and economic benefits.It also helphospital managers to find the weak point, adjust organization structure and management strategy, optimize the allocation of resources, improve operational efficiency, enhance the comprehensive competitiveness of the hospital. Hospital is the main part of the health system, is also the objectpart to implement medical treatmentand ensure people's health.Surgical doctor is the core productivityof thehospital,is the core competitiveness of the hospitalwhich affecting the long-term development of the hospital. So based on the present situation of hospital performance managementto study surgicaldoctor performance appraisal system has positive significance. According to the analysis of current surgicaldoctor performance management at home and abroad, this thesisdiscusses the theoretical results ofsurgicaldoctor performance evaluation system, using the method of literature review, expert consultation, historical data analysis, mathematical statisticsandcombination with quantitative and qualitative method,andreference for balanced score card(BSC), KPI and Delphi theory ,to build the current surgicaldoctor performance management system of Z hospital.The surgicaldoctor performance appraisalsystem of Z hospital can help to promote the overall management level, realizethe goal of increasing social benefits and economic benefits at the same time, it also provides positive reference value for other comprehensive hospitals.